Stress Response and Pathogenicity of the Necrotrophic Fungal Pathogen Alternaria alternata - Kuang-Ren Chung (Scientifica)
The production of host-selective toxins by the necrotrophic fungus Alternaria alternata is essential for the pathogenesis. A. alternata infection in citrus leaves induces rapid lipid peroxidation, accumulation of hydrogen peroxide (H2O2), and cell death. The mechanisms by which A. alternata avoids killing by reactive oxygen species (ROS) after invasion have begun to be elucidated. The ability to coordinate of signaling pathways is essential for the detoxification of cellular stresses induced by ROS and for pathogenicity in A. alternata. A low level of H2O2, produced by the NADPH oxidase (NOX) complex, modulates ROS resistance and triggers conidiation partially via regulating the redox-responsive regulators (YAP1 and SKN7) and the mitogen-activated protein (MAP) kinase (HOG1) mediated pathways, which subsequently regulate the genes required for the biosynthesis of siderophore, an iron-chelating compound. Siderophore-mediated iron acquisition plays a key role in ROS detoxification because of the requirement of iron for the activities of antioxidants (e.g., catalase and SOD). Fungal strains impaired for the ROS-detoxifying system severely reduce the virulence on susceptible citrus cultivars. This paper summarizes the current state of knowledge of signaling pathways associated with cellular responses to multidrugs, oxidative and osmotic stress, and fungicides, as well as the pathogenicity/virulence in the tangerine pathotype of A. alternata.